The Principal's Strategy for Fostering Morals and Worship Culture at Taruna Islamic Elementary School in Surabaya - Nasiri (STID Raudlatul Iman Sumenep, 2023)
The principal is the educational leader at the school level and is responsible for the progress and decline of the school they lead. They are required to possess management and leadership skills to develop and advance their school effectively, efficiently, independently, productively, and accountably. The topic,